DETERMINING THE FAVORABLE AREA FOR THE CREATION OF A “PARK AND RIDE” ARRANGEMENT, IN THE EASTERN PART OF CLUJ-NAPOCA MUNICIPALITY USING GIS TECHNOLOGY - HĂRĂNGUŞ, Iulia; RETEGAN, Violeta-Elena (Studia Universitatis Babeș-Bolyai Geographia, 2019)
At present, population mobility is not a choice, it is a necessity, and with the economic development of the city, the population growth of metropolitan and non-metropolitan areas working in the urban environment and the inefficiency of the public transport system, people have become dependent on cars. Traffic congestion remains one of the problems of Cluj-Napoca municipality and continues to be a major concern for researchers. Extra-urban mobility has a significant role in the structure of city traffic. The study aims to highlight two increasingly important features of population mobility research, intermodality and multimodality. Therefore, on the basis of the geomorphological evaluation, the sites in the eastern part of the city where it is possible to create an intermodal passenger center, which will benefit from all the functional transport means in the city, will be analyzed. Thus, this area would become a metropolitan and non-metropolitan area reception center, and at the same time an alternative for individual motorized transport, promoting a sustainable form of mobility of the extra-urban population. An integrated component of many public transport systems in developed countries, “Park and Ride” support the planners’ effort to eliminate as many vehicles as possible from the daily traffic. The geomorphological studies made in the study area, namely the southern slope of St. Gheorghe Hill, are numerous in the last 50 years (Morariu et al., 1967; ISPIF project for soil erosion in the northern area of Cluj-Napoca, 1986; Surdeanu et al., 2006; Poszet, 2011, etc.). The results of the previous geomorphological research reveal the fact that this territory presents a dynamic of the moderate slopes, due to the efficiency of the land improvement works. However, certain sections of the slope are found to accelerate landsides and torrential erosion in surface, especially in terraced areas. This is not, however, an impediment to finding solutions to problems such as the one mentioned above. Taking into account the intense expansion of Cluj-Napoca, especially in the West-East direction, the most suitable place for arranging such a car park is in the eastern part of a city. An argument in favor of this option is that in this urban area the degree of occupancy of buildings or infrastructure is lower compared to other sectors. The sustainability of the territory for such an arrangement will be determined on the basis of morphological indicators specific to a risk study. The paper develops a GIS-based approach to assess the area as favorable as possible for the creation of a “Park and Ride” arrangement both geomorpho-logically and in terms of population mobility.